Analisis penerapan sistem akuntabilitas kinerja instansi pemerintah berdasarkan Peraturan Presiden Nomor 29 Tahun 2014 pada Badan Pendapatan Daerah Provinsi Sulawesi Utara - Ritto, Fanesia; Budiarso, Novi Swandari; Sardjono , Olivia Y.M. (Yayasan Widyantara Nawasena Raharja, 2025)
The Government Agency Performance Accountability System is a system whose application is used to measure performance against the level of success and failure in programs and activities. In this case, Presidential Regulation Number 29 of 2014 concerning the Performance Accountability System of Government Agencies which is the basis for the regulation on the implementation of SAKIP. In this regulation, the implementation of SAKIP consists of Strategic Plan, Performance Agreement, Performance Measurement, Performance Data Management, Performance Data Reporting, Performance Reporting, and Review and Evaluation. This study aims to determine the suitability of the implementation of SAKIP based on Presidential Regulation No. 29 of 2014 and to determine the level of success and failure of programs and activities that have been determined. The methods used in this study are qualitative descriptive and data collection methods through interviews and documentation. The results of this study show that the implementation of the Government Agency Performance Accountability System at the North Sulawesi Provincial Regional Revenue Agency has been good and in accordance with Presidential Regulation Number 29 of 2014.